11th North American Caribou Workshop, 24-27 April 2006, Jasper, Alberta, Canada. - Haugerud (editor in chief), Rolf Egil; McCutchen (iss. eds.), Nicole (Rangifer, 2007)
Proceedings - The 11th North American Caribou Workshop, Jasper, Alberta, Canada, 24-27 April, 2006